Learning Model And Logical Thinking Ability in Redox Reaction Learning - Gulmah Sugiharti*; Wan Azura (Universitas Syiah Kuala, 2021)
The implementation of the 2013 curriculum has not been fully implemented in Private High School Angkasa Medan , because teachers do not fully understand the learning model that must be used. This has an impact on the results of student chemistry learning that not all students are able to achieve the set minimum completeness score target of 75. This study is about the application of learning models and the ability to think logically in redox learning in class X Private High School Angkasa Medan. The population consisted of 6 class X students and the sample was taken purposively by setting 2 classes for the research sample. Both classes are taught with two models, with a combination of factorial 2 X 2. There are two factors tested, namely factor A in the form of a learning model consisting of Problem Based Learning (PBL) and Direct Instruction (DI) models, factor B: logical thinking ability high and low logical thinking ability. Data analysis techniques using 2-way ANOVA. Based on the hypothesis test at a significant level of α = 0.05, it shows that there is an influence of the learning model and students' logical thinking ability on the learning outcomes of topic redox chemistry, and there is an interaction between the learning model and the ability to think logically towards the redox learning outcomes. The results of the BNT advanced test indicate that the Problem Based Learning Model is better than the Direct Instruction model on topic redox chemistry learning.